Impulsionando a gestão: desafios e estratégias em organizações não governamentais no município de Manaus - AM - Ciacci, Iandra Brandão (Brasil, 2024)
This article analyses the management practices adopted by managers of non-governmental organisations (NGOs) in Manaus/AM, and identifies the main challenges and strategies faced in the context of managing these entities. To this end, interviews were conducted with 12 individuals from different organisations who held leadership, management and administrative support positions in these institutions. NGOs with at least 9 years of operation were considered. The data was analysed according to Bardin (2016) and processed using the IRAMUTEQ software (Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires). This procedure classified the most relevant terms in the interviewees' statements into seven categories: People, Organisational Resources, Sustainability, Meaning, Communication and Operational Continuity. The analysis highlighted the importance of human capital, with an emphasis on attracting people aligned with the NGO's values and missions. The main challenge identified was financial sustainability, aggravated by the constant need to raise funds, requiring effective strategies to ensure the survival and development of NGOs.